A trait‐based rapid assessment framework to estimate fire impacts on data‐poor Australian invertebrate taxa - Jessica R. Marsh; Payal Bal; Libby Rumpff; John C. Z. Woinarski (Conservation Biology, 2026)
Following large‐scale threatening events, a key challenge is to rapidly establish which species have been most affected and are in need of urgent conservation. For data‐poor taxa, such assessments are challenging. In Australia, invertebrates represent over 90% of faunal diversity and are critical for ecosystem function, yet most are undescribed, and, of the described, most are poorly known. Thus, it is important to have a way to estimate susceptibility to major disturbance of data‐deficient taxa. We developed a novel trait‐based method for assessing the impact of a major wildfire on invertebrates. We applied it to 1220 species that showed high distributional overlap with the 2019–2020 Australian megafires. We estimated susceptibility based on the microhabitat species occupy, their life‐history and ecological traits, and mechanisms that account for key data uncertainties (number of usable occurrence records, availability of traits data, and recency of taxonomic work). We found 748 species likely to be of potential conservation concern following the megafires; 169, 579, and 454 were highly, moderately, and mildly threatened by a major fire, respectively. Most species (867) were associated with poor or very poor data quality. Of the 867 poorly known species, 97 were most at risk from a major fire. Our approach is generalizable to other data‐deficient taxa and to major disturbance events globally and can be used to improve representation of poorly known species in conservation assessments and threat mitigation decisions. If the uncertainties and knowledge gaps we identified are addressed, it is likely risk prediction could be improved.

LP-19 ABCB1 rs2032582 and Plasma Norbuprenorphine Levels in Opioid Use Disorder - M. Tepe; S.A. Yıldırım; S. Özkan-Kotiloğlu; C. Bal; M. Danışman; E. Demirbaş; D. Kaya-Akyüzlü (Toxicology Letters, 2025)

P04-08 Association Between GHRL rs696217 Polymorphism and Acylated Ghrelin Levels in Women with Polycystic Ovary Syndrome - D. Kaya-Akyüzlü; S. Özkan-Kotiloğlu; M.A. Yıldırım; C. Bal; G. Gök; R. Desdicioğlu; A.F. Yavuz (Toxicology Letters, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Reproductive Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Regulatory Toxicology and Pharmacology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Food and Chemical Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Chemico-Biological Interactions, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Toxicology Letters, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Environmental Toxicology and Pharmacology, 2025)

Comparative in vitro and in silico analysis of the ability of basic Asp49 phospholipase A2 and Lys49-phospholipase A2-like myotoxins from Bothrops diporus venom to inhibit the metastatic potential of murine mammary tumor cells and endothelial cell tubulogenesis - Daniela J. Sasovsky; Emilio Angelina; Laura C. Leiva; Elisa Bal de Kier Joffé; Bruno Lomonte; Soledad Bustillo (Chemico-Biological Interactions, 2024)

S05-01 Functional mapping of neurodevelopmental disorders to ontology-based DNT NAMs for Next Generation Risk Assessment of chemicals - E. Kuchovska; L. Ladeira; K. Bartmann; D. Polozij; N. Gorts; E. Corek; A. Donmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; A. Gamba; et al. (Toxicology Letters, 2024)

Heterotrophic bacteria isolated from a chloraminated system accelerate chloramine decay - Vimala Seenivasagham; Bal Krishna K C; Joseph P. Chandy; George Kastl; Linda L. Blackall; Bruce Rittmann; Arumugam Sathasivan (Chemosphere, 2024)

Modeling of Tunnel Boring Machine Performance Employing Random Forest Algorithm - C. Gokceoglu; C. Bal; C. H. Aladag (Geotechnical and Geological Engineering, 2023)

Accounting for the neglected: Invertebrate species and the 2019–2020 Australian megafires - Jessica R. Marsh; Payal Bal; Hannah Fraser; Kate Umbers; Tanya Latty; Aaron Greenville; Libby Rumpff; John C. Z. Woinarski (Global Ecology and Biogeography, 2022)
Aim Invertebrates make up the vast majority of fauna species but are often overlooked in impact assessment and conservation response. The extent to which the 2019–2020 Australian megafires overlapped with the range of vertebrate species has been well documented; consequently, substantial resourcing has been directed towards their recovery. Here, we attempt to document the extent of overlap of these megafires with invertebrate species. In doing so, we seek to demonstrate that it is possible and worthwhile to assess the effect of a catastrophic event on a large number of poorly known species. Location Temperate and subtropical Australia. Time period 2019–2020. Major taxa Australian invertebrates. Methods We adapted a published analytical pathway for the assessment of distributional fire overlap on vertebrate species. Overlaps with fire for 32,163 invertebrate taxa were determined using point records and polygons. Results We found that 13,581 invertebrate taxa had part of their range burnt in the 2019–2020 Australian megafires. Of these, 382 taxa had the whole of their known range burnt, and a further 405 taxa had 50–99.9% of their range burnt. Five examples are described. Main conclusions Poorly known groups of biodiversity can be impacted significantly by major disturbance events, but such impact is often overlooked. This oversight has the consequences of under‐estimating the magnitude of impacts and the potential failure to direct conservation responses to those species most in need of them. Our analysis demonstrates that the 2019–2020 megafires burnt ≥50% of the known range of nearly 800 Australian invertebrate taxa, a tally far higher than for vertebrates (19 taxa). Assessment of the real impact (i.e., beyond simply overlap with fire) requires more consideration of susceptibility and/or post‐fire survey and monitoring. The magnitude of overlap of the 2019–2020 megafires on invertebrate species justifies a conservation response that is less biased towards iconic vertebrate species.

Correction to: Observations from the March 2021 Thessaly Earthquakes: an earthquake engineering perspective for masonry structures - V. Sarhosis; C. Giarlelis; C. Karakostas; E. Smyrou; I. E. Bal; S. Valkaniotis; A. Ganas (Bulletin of Earthquake Engineering, 2022)

Observations from the March 2021 Thessaly Earthquakes: an earthquake engineering perspective for masonry structures - V. Sarhosis; C. Giarlelis; C. Karakostas; E. Smyrou; I. E. Bal; S. Valkaniotis; A. Ganas (Bulletin of Earthquake Engineering, 2022)
Two strong earthquakes hit Thessaly region on March 3rd, 2021 (M w = 6.3) and on March 4th, 2021 (M w = 6.1). The epicentres of the earthquakes were located at approximately 23 and 29 km respectively NW of Larissa, one of the most populous cities in Greece. Several aftershocks followed thereafter. Although no injuries were recorded, several structures suffered significant damage close to the epicentre, while some others collapsed. Approximately 300 residents of the village of Damasi were transferred to temporary settlements and tents. The event occurred during the COVID19 lockdown and created significant stress and disruption to residents. This paper focuses on the earthquake swarm itself as well as the damages observed in residential buildings, schools, and churches in the earthquake-stricken region. The earthquakes mainly impacted low-rise domestic masonry buildings, while the more modern reinforced concrete structures built following the recent seismic regulations were almost unaffected. The typology of buildings in the region, together with photographs demonstrating the extent of damage are presented herein. Despite the rather satisfactory performance of modern buildings in recent earthquakes in Greece, the preliminary investigations from the Thessaly Earthquakes showed that there is still a significant level of vulnerability in existing masonry building stock constructed using traditional methods and materials. This issue could re-emerge in future earthquakes striking other rural areas of Greece, something that needs to be addressed systematically in the future.

Missing Data in Sea Turtle Population Monitoring: A Bayesian Statistical Framework Accounting for Incomplete Sampling - Lucy C. M. Omeyer; Trevelyan J. McKinley; Nathalie Bréheret; Gaëlle Bal; George Petchell Balchin; Abdon Bitsindou; Eva Chauvet; Tim Collins; Bryan K. Curran; Angela Formia; Alexandre Girard; Marc Girondot; et al. (Frontiers in Marine Science, 2022)
Monitoring how populations respond to sustained conservation measures is essential to detect changes in their population status and determine the effectiveness of any interventions. In the case of sea turtles, their populations are difficult to assess because of their complicated life histories. Ground-derived clutch counts are most often used as an index of population size for sea turtles; however, data are often incomplete with varying sampling intensity within and among sites and seasons. To address these issues, we: (1) develop a Bayesian statistical modelling framework that can be used to account for sampling uncertainties in a robust probabilistic manner within a given site and season; and (2) apply this to a previously unpublished long-term sea turtle dataset (n = 17 years) collated for the Republic of the Congo, which hosts two sympatrically nesting species of sea turtle (leatherback turtle [ Dermochelys coriacea ] and olive ridley turtle [ Lepidochelys olivacea ]). The results of this analysis suggest that leatherback turtle nesting levels dropped initially and then settled into quasi-cyclical levels of interannual variability, with an average of 573 (mean, 95% prediction interval: 554–626) clutches laid annually between 2012 and 2017. In contrast, nesting abundance for olive ridley turtles has increased more recently, with an average of 1,087 (mean, 95% prediction interval: 1,057–1,153) clutches laid annually between 2012 and 2017. These findings highlight the regional and global importance of this rookery with the Republic of the Congo, hosting the second largest documented populations of olive ridley and the third largest for leatherback turtles in Central Africa; and the fourth largest non-arribada olive ridley rookery globally. Furthermore, whilst the results show that Congo’s single marine and coastal national park provides protection for over half of sea turtle clutches laid in the country, there is scope for further protection along the coast. Although large parts of the African coastline remain to be adequately monitored, the modelling approach used here will be invaluable to inform future status assessments for sea turtles given that most datasets are temporally and spatially fragmented.

Spectral Signature-Based Water Stress Characterization and Prediction of Wheat Yield under Varied Irrigation and Plant Bio-regulator Management Practices - Santanu Kumar Bal; G. C. Wakchaure; Sunil Potekar; Burhan U. Choudhury; Ram Lal Choudhary; Rabi Narayan Sahoo (Journal of the Indian Society of Remote Sensing, 2021)

Effect of IW:CPE-Based Irrigation Scheduling and N-Fertilization Rate on Yield, Water and N-Use Efficiency of Wheat (Triticum aestivum) - R. L. Choudhary; P. S. Minhas; G. C. Wakchaure; S. K. Bal; P. Ratnakumar (Agricultural Research, 2021)

Characteristics of the Indian Summer Monsoon Rainfall Simulated by the Regional Climate Model (RegCM4) - Prasanta Kumar Bal; Sarat C. Kar (Pure and Applied Geophysics, 2020)

Targeted Intravenous Nanoparticle Delivery: Role of Flow and Endothelial Glycocalyx Integrity - Ming J. Cheng; Ronodeep Mitra; Chinedu C. Okorafor; Alina A. Nersesyan; Ian C. Harding; Nandita N. Bal; Rajiv Kumar; Hanjoong Jo; Srinivas Sridhar; Eno E. Ebong (Annals of Biomedical Engineering, 2020)

Novel and recurrent variants of ATP2C1 identified in patients with Hailey-Hailey disease - J. Sawicka; A. Kutkowska-Kaźmierczak; K. Woźniak; A. Tysarowski; K. Osipowicz; J. Poznański; A. M. Rygiel; N. Braun-Walicka; K. Niepokój; J. Bal; C. Kowalewski; K. Wertheim-Tysarowska (Journal of Applied Genetics, 2020)
Hailey-Hailey disease (HHD) is a rare, late-onset autosomal dominant genodermatosis characterized by blisters, vesicular lesions, crusted erosions, and erythematous scaly plaques predominantly in intertriginous regions. HHD is caused by ATP2C1 mutations. About 180 distinct mutations have been identified so far; however, data of only few cases from Central Europe are available. The aim was to analyze the ATP2C1 gene in a cohort of Polish HHD patients. A group of 18 patients was enrolled in the study based on specific clinical symptoms. Mutations were detected using Sanger or next generation sequencing. In silico analysis was performed by prediction algorisms and dynamic structural modeling. In two cases, mRNA analysis was performed to confirm aberrant splicing. We detected 13 different mutations, including 8 novel, 2 recurrent (p.Gly850Ter and c.325-3 T > G), and 6 sporadic (c.423-1G > T, c.899 + 1G > A, p.Leu539Pro, p.Thr808TyrfsTer16, p.Gln855Arg and a complex allele: c.[1610C > G;1741 + 3A > G]). In silico analysis shows that all novel missense variants are pathogenic or likely pathogenic. We confirmed pathogenic status for two novel variants c.325-3 T > G and c.[1610C > G;1741 + 3A > G] by mRNA analysis. Our results broaden the knowledge about genetic heterogeneity in Central European patients with ATP2C1 mutations and also give further evidence that careful and multifactorial evaluation of variant pathogenicity status is essential.

Experimental and analytical studies of sub-standard RC frames retrofitted with buckling-restrained braces and steel frames - Fatih Sutcu; Ahmet Bal; Kazuhiro Fujishita; Ryota Matsui; Oguz C. Celik; Toru Takeuchi (Bulletin of Earthquake Engineering, 2020)

Development and analysis of an adverse outcome pathway network for human neurotoxicity - Nicoleta Spinu; Anna Bal-Price; Mark T. D. Cronin; Steven J. Enoch; Judith C. Madden; Andrew P. Worth (Archives of Toxicology, 2019)

Relation Between Lung Dysfunction and Blood Cadmium and Lead Levels Among Welders - S. P. Cetintepe; S. B. Iritas; M. Gunduzoz; M. E. Alaguney; D. Wilson; C. Bal; O. H. Yilmaz; L. Tutkun; Eun-Kee Park (Exposure and Health, 2019)

Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - H. Ram; A. Rashid; W. Zhang; A. P. Duarte; N. Phattarakul; S. Simunji; M. Kalayci; R. Freitas; B. Rerkasem; R. S. Bal; K. Mahmood; E. Savasli; et al. (Plant and Soil, 2016)

Novel sporadic and recurrent mutations in KRT5 and KRT14 genes in Polish epidermolysis bullosa simplex patients: further insights into epidemiology and genotype–phenotype correlation - K. Wertheim-Tysarowska; M. Ołdak; A. Giza; A. Kutkowska-Kaźmierczak; J. Sota; D. Przybylska; K. Woźniak; D. Śniegórska; K. Niepokój; A. Sobczyńska-Tomaszewska; A. M. Rygiel; R. Płoski; et al. (Journal of Applied Genetics, 2016)

Erratum to: Elephants Also Like Coffee: Trends and Drivers of Human–Elephant Conflicts in Coffee Agroforestry Landscapes of Kodagu, Western Ghats, India - P. Bal; C. D. Nath; K. M. Nanaya; C. G. Kushalappa; C. Garcia (Environmental Management, 2011)

Elephants Also Like Coffee: Trends and Drivers of Human–Elephant Conflicts in Coffee Agroforestry Landscapes of Kodagu, Western Ghats, India - P. Bal; C. D. Nath; K. M. Nanaya; C. G. Kushalappa; C. Garcia (Environmental Management, 2011)

Combining QTL mapping and transcriptome profiling of bulked RILs for identification of functional polymorphism for salt tolerance genes in rice (Oryza sativa L.) - Awadhesh Pandit; Vandna Rai; Subhashis Bal; Shikha Sinha; Vinod Kumar; Mahesh Chauhan; Raj K. Gautam; Rakesh Singh; Prakash C. Sharma; Ashok K. Singh; Kishor Gaikwad; Tilak R. Sharma; et al. (Molecular Genetics and Genomics, 2010)

Protein kinase C δ inhibits the production of proteolytic enzymes in murine mammary cells - Valeria C. Grossoni; Karina B. Falbo; Laura V. Mauro; Martín A. Krasnapolski; Marcelo G. Kazanietz; Elisa D. Bal De Kier Joffé; Alejandro J. Urtreger (Clinical & Experimental Metastasis, 2007)

Cigarette Smoking Among Lesbians, Gays, and Bisexuals: How Serious a Problem? (United States) - Hao Tang; Greg L. Greenwood; David W. Cowling; Jon C. Lloyd; April G. Roeseler; Dileep G. Bal (Cancer Causes & Control, 2004)

Founder effect for a 26-bp deletion in the RFXANK gene in North African major histocompatibility complex class II-deficient patients belonging to complementation group B - W. Wiszniewski; M. -C. Fondaneche; N. Lambert; K. Masternak; C. Picard; L. Notarangelo; K. Schwarz; J. Bal; W. Reith; C. Alcaide; G. de Saint Basile; A. Fischer; et al. (Immunogenetics, 2000)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

Resting sporangium of Synchytrium endobioticum: its structure and composition of the lipids and fatty acids - Arya K. Bal; Arun C. Dey; Michael C. Hampson (Archives of Microbiology, 1984)